Edukasi Pencegahan Corona Virus Disease (Covid19) dalam Menghadapi New Normal melalui Whatsapp Group di Desa Pematang Lumut Kecamatan Betara - Faridah Faridah; Iin Indrawati (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2022)
The rise of the spread of covid-19 in the world, including Indonesia, especially in Pematang Lumut Village, Tangung Jabung Barat Regency, Jambi Province, worries all parties. Corona virus is a pandemic disease in 2019, where one of the handling and prevention can be done by complying with health protocols. Community service activities were carried out in November-December 2020 with a discussion method and conveying material and pictorial posters related to the corana virus sent via Whatsapp Group. In this pictorial poster there are 4 things, namely (1) Education about Covid-19, (2) Good and Correct Hand Washing Methods, (3) Social Distancing, (4) How to Use Masks. This community service activity begins with a pre-test and ends with a post-test online survey regarding the level of compliance with health protocols during the new normal. This Community Service (PKM) aims to be used as a source of knowledge for the people of Pematang Lumut Village, Betara District, Tanjung Jabung Barat Regency, and can help pay more attention to and comply with health protocols in undergoing New Normal. The results of this activity which were evaluated both through Google Form and the question and answer via Whatsapp Group, were that the average community was satisfied and experienced an increase in understanding of COVID-19 prevention by complying with health protocols.